The Effect of Adding White Tumeric (Curcuma zedoaria) Extract on the Immune System of Vaname Shrimp (Litopenaeus vannamei) Tested Against Vibrio harveyi Bacteria - Azilia Rosyida; Dewi Nur'aeni Setyowati; Fariq Azhar (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
The entry of vaname shrimp into Indonesia was to replace tiger prawns (Penaeus monodon) which at that time experienced a decline in quality. Although vaname shrimp is famous for having various advantages, there are still obstacles encountered during the cultivation period, one of which is the attack of vibriosis caused by the bacterium Vibrio harveyi. This study aims to determine the effect of adding white turmeric extract (Curcuma zedoaria) on the immune system of white shrimp (Litopenaeus vannamei) which was challenged with Vibrio harveyi bacteria. This research was conducted for 60 days from March to May 2021 using experimental research methods. The research container used a container container (size 40x30x28 cm) and a stocking density of 20 fish/container with a volume of 20 L. The research design used was a completely randomized design consisting of 5 treatments with 3 replications where P1: artificial feed + Vibrio harveyi infection, P2: artificial feed + 0.1 mL NaCl injection, P3: artificial feed + 0,5% white turmeric extract + V.harveyi infection, P4: Artificial Feed + 1% white turmeric extract + V.harveyi infection, P5: Artificial feed + 2% white turmeric extract + V.harveyi infection. The results showed that administration of white turmeric extract (C.zedoaria) with a dose of 1% gave the best results and had a significant effect on the survival rate of 68.3%, Total Haemocyte Count of 21.63x10⁶ cells/mL, and Differential Haemocyte Count (hyaline cells). by 58.7%, semi-granulocytes by 18.33%, granulocytes by 23%) which play a role in the immune system of white vaname shrimp. In addition, the value of phagocytic activity was 68.8% and was able to suppress the growth of bacteria in the intestine at the lowest at 57.7×108 CFU/mL and suppress the number of vibrios to the lowest number at 26×106 CFU/mL